Kesulitan Keuangan, Integritas Manajemen, Profesionalisme, dan Ketergantungan Pengguna Eksternal Laporan Keuangan terhadap Risiko Audit - Lutfiana Nur Hanifah; Siti Noor Khikmah; Faqiatul Mariya Waharini (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2020)
This study aims to examine the effect of financial difficulties, management integrity, professionalism, and the dependence of external users of financial statements on audit risk. The researcher uses a sample of auditors working at public accounting firms in the Central Java and Yogyakarta regions. selected based on purposive sampling method with criteria, namely, auditors who have a minimum of a bachelor's degree and have a working period of more than one year. Hypothesis testing in this study uses multiple linear regression. The results show that financial difficulties have a positive effect on audit risk, while management integrity, professionalism and dependency of external users of financial statements are proven to have no effect on audit risk.